ASSET LIABILTY MANAGEMENT IN SHARIA BANK - Umi, Umi Indasyah Zahro; Sadad, Ahmad Musadad; Mustaniroh, Mustaniroh; Tri Pujiati (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
Islamic banks are financial institutions that act as intermediaries or liaisons for parties with surplus funds and deficit funds. Islamic banks need a strategy in managing their assets and liabilities in order to obtain net income for the bank itself. The tight competition between Islamic banks and conventional banks and the increasing number of banks in Indonesia, so all banks strive to improve their quality and management, so the people trust and use the services of the bank. System banking which is part from system finance will influence the running of the economic system. This study aims to explain asset and liability management in Islamic banks both in terms of theory and its application. This study uses a qualitative descriptive approach using a literature study to obtain research data related to asset and liability management in Islamic banks. The results of this study indicate that Islamic banking has different asset and liability components from conventional banking and the risks it faces. The application of ALMA ( Asset Liability Management ) in Islamic banks relies more on asset quality and this will determine the bank’s ability to increase customer attraction to invest their funds in Islamic banks. The results of this study can be implemented in Islamic banks to improve the quality of their liability management through good management and the application of ALMA in the management of Islamic banks